On Unambiguous Nondeterministic Finite Automata and the Strict Tree Property. - Adorna, Henry (Philippine computing journal)
In this paper, We intend to discuss the class of automata between deterministic finite automata (DFA) and unambiguous nondeterministic ñnite automata (UFA), which has the strict tree property. We call this class the Strict Unambiguous Finite Automata (StUFA)1. A reasonable characterization of these automata based on the transition relation A will be provided.